The framing effects of multipart pricing on consumer purchasing behavior of customized information good bundles - Bockstedt, Jesse C. (2013)
Applying behavioral economic theories, we hypothesize that consumers have sticky reference prices for individual information goods, but their perceived value for customizable bundle offers can be significantly influenced by the framing of a multipart pricing scheme. The potential impacts of these framing effects are measurable changes in consumer behavior and sales outcomes. We conducted a series of behavioral experiments and a large-scale natural field experiment involving actual purchases of customized information good bundles to confirm and analyze the hypothesized effects. The results demonstrate a consumer's willingness to purchase a customized bundle of information goods, the size of the resulting bundling, and the consumer's perceptions of the transaction are each significantly influenced by the design of the multipart pricing scheme. These results hold even when the final price and size of a customized bundle are the same across differing schemes. We discuss the potential tradeoffs in economic outcomes that result from price framing (e.g., likelihood of sale versus size of purchased bundles) and the implications for information good retailers.